2004
DOI: 10.1023/b:requ.0000042343.64831.32
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Distributions and News: Evidence from Index Options

Abstract: We estimate the shape of the distribution of stock prices using data from options on the underlying asset, and test whether this distribution is distorted in a systematic manner each time a particular news event occurs. In particular we look at the response of the FTSE100 index to market wide announcements of key macroeconomic indicators and policy variables. We show that the whole distribution of stock prices can be distorted on an event day. The shift in distributional shape happens whether the event is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…The empirical literature on the effects of macroeconomic news announcements on stock prices has an extensive history, for example, Brealey (1970), Officer (1973), Rozeff (1974, Goodhart and Smith (1985), Campbell (1987), Cutler et al (1989), Schwert (1989a,b) and Wasserfallen (1989). More recent contributions to the literature relating conventional monetary policy surprises and other macroeconomic news on returns in stock markets and volatility in stock markets both within and across countries include, Becker (1995), Hamilton and Lin (1996), Bomfim (2003), Ederington and Lee (1993), Steeley (2004), Graham et al, (2003), Kearney and Lombra (2004), Nikkinen and Sahlström (2001, 2004a, 2004b, Brenner et al (2009) and Bekaert et al (2013). 3 Our paper adds to this literature by examining the impact of monetary policy actions during the recent crisis and QE phases on the volatility of and cross correlations between the UK and US equity markets.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The empirical literature on the effects of macroeconomic news announcements on stock prices has an extensive history, for example, Brealey (1970), Officer (1973), Rozeff (1974, Goodhart and Smith (1985), Campbell (1987), Cutler et al (1989), Schwert (1989a,b) and Wasserfallen (1989). More recent contributions to the literature relating conventional monetary policy surprises and other macroeconomic news on returns in stock markets and volatility in stock markets both within and across countries include, Becker (1995), Hamilton and Lin (1996), Bomfim (2003), Ederington and Lee (1993), Steeley (2004), Graham et al, (2003), Kearney and Lombra (2004), Nikkinen and Sahlström (2001, 2004a, 2004b, Brenner et al (2009) and Bekaert et al (2013). 3 Our paper adds to this literature by examining the impact of monetary policy actions during the recent crisis and QE phases on the volatility of and cross correlations between the UK and US equity markets.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In Table 4.6 we can also see that the coefficients of the aggregate dummy variable is negative in all cases and hence, news announcements reduce implied volatility. This is consistent with the findings of the literature on the effect of news announcements on implied volatility (see e.g., Patell and Wolfson, 1979, Donders and Vorst, 1996, Ederington and Lee, 1996, Fornari and Mele, 2001, Kim and Kim, 2003, Fornari, 2004, Steeley, 2004, Beber and Brandt, 2006, Äijö, 2008 and implied volatility indices within a single-country setting (see e.g., Nikkinen and Sahlström, 2001, 2004a. Interestingly, it is in contrast with the findings on the reaction of volatility measures other than implied volatility to news releases (see e.g., Jones et al, 1998, who document that the conditional volatility in bond markets increases on the announcement day).…”
Section: Aggregate News Releases: Announcement and Surprise Effectssupporting
confidence: 92%
“…From a theoretical point of view, news releases are expected to affect volatility; Ross (1989) showed that in the absence of arbitrage ,the instantaneous variance of returns equals the variance of information flow. In addition, the empirical evidence has documented that implied volatility drops as soon as a scheduled news announcement is released (see e.g., Patell and Wolfson, 1979, Donders and Vorst, 1996, Ederington and Lee, 1996, Fornari and Mele, 2001, Kim and Kim, 2003, Fornari, 2004, for an examination of at-the-money implied volatility, and Steeley, 2004, Beber and Brandt, 2006, Äijö, 2008, for an examination of the second moment of option implied risk-neutral distributions). 21 This finding is consistent with the models of implied volatility behavior around scheduled news announcements suggested by Patell and Wolfson (1979), and Ederington and Lee (1996) that predict that implied volatility falls on scheduled news announcement days.…”
Section: Introductionmentioning
confidence: 99%
“…This is in similar fashion to established findings in the efficiency market hypothesis. Recent evidence that supports this includes (Steeley 2004;Kadapakkam et al 2015).…”
Section: Introductionmentioning
confidence: 96%